Impact of solar power generation on building distribution network - Lim, Sylvia Po Hong. (2013)
Renewable resources have been greatly adopted in many countries to generate electricity due to its benefits to our environments. However there are many different renewable resources can be used to generate electricity such as wind, water and hence before deciding the suitable resources to use in that location, we have to study the areas such as the limitation of the renewable resource on that particular location. Among these renewable resources, solar energy is the most contributors in Singapore hence installing of photovoltaic system is the best option. Photovoltaic system converts the solar energy into electrical energy without emitting greenhouse gases. For designing of the installation of a photovoltaic systems, there are many factors need to be concerns such as the site location where it determine the amount of sunlight can be received, tilt angle of the panel to be able to receive the sunlight with minimum losses and shading from the obstacles that restrict its capability of generating the electricity. And the operation of each component in the PV system for the conversion process from the incoming sunlight till to the load ends.